Drama in the mixed-ability EFL classroom : observing its effects on motivation and self-confidence - Bess Renee Neal 1980- (2012)
This study is a result of experimenting with the use of drama to teach English as a foreign language in Iceland with special attention placed on a mixed-ability classroom environment. It begins with a comprehensive review of research pertaining to the use of drama for the instruction of English as a foreign language. It then examines my experience in the classroom through personal observation and unstructured interviews. The discussion focuses on the main benefits to using drama in the EFL classroom including increasing students’ motivation and self-confidence, as well as meeting the aims of communicative language teaching. Finally, I explore and discuss teachers’ fears about drama and make recommendations. keywords: EFL, drama, motivation, mixed-ability, self-confidence, inclusive education, active learning